Avaliação física, físico-química e sensorial de cultivares alface produzidas em diferentes sistemas de cultivo - Fontana, Larissa (2016)
In Brazil, there is a growing and promising market that explores the new cultivars of lettuce and crispy segment the Brunella and Crocantella cultivars are examples. The cv. Brunella is an innovative cultivar that combines crisp lettuce characteristics and lettuce being adapted to Brazilian culture conditions. A cv. Crocantella is also included in this segment. It is considered a vigorous lettuce with high numbers of leaves, heavy, thick and light green. The lettuce cultivation may be performed in different cropping systems they are different from each other in crop management and also in post-harvest handling. These differences often produce lettuces with physical, physico-chemical and sensory differentiated. In this way the objective of this study was to determine the effect of different cropping systems in physical, physicochemical and sensory parameters in lettuce cultivars. For cv. Brunella noted that the plant produced hydroponically provided with larger lettuce leaves. The organic plant increased loss of weight. It was not found statistically significant differences for turgor pressure loss analysis among the three cropping systems.The instrumental analysis color demonstrated that hydroponic lettuce presented lighter green that produced the organic system and higher acidity compared to the other two systems. Not found a statistically significant difference in the measurement of soluble solids and total phenolic compounds among the three cropping systems. The sensory analysis cv. Brunella organic was the one with lowest preference and intention to purchase by the consumer. For cv. Crocantella was found that for conventional lettuce leaf area showed higher, then the hydroponic and organic, with significant difference between them. The sample produced in the organic system had lower leaf area, lower ULA and lower initial fresh and even the loss of weight was significantly higher when compared to the other two cropping systems. There was no significant statistical difference in the turgidity initial values, final and loss of turgor pressure between the samples produced in the three cropping systems. In instrumental analysis of color it was also no statistically significant difference among the three cropping systems. The physicochemical analysis was not statistically significant differences in pH values between samples produced in the three cropping systems.The organic sample obtained highest soluble solids, with difference to the hydroponic system. In the determination titratable acidity and total phenolic compounds was obtained statistically significant differences between the three systems. For titratable acidity hydroponic sample had higher acidity, then the organic sample and the conventional sample, for the determination of total phenolic compounds, organic sample had a higher value, then the hydroponic and conventional. With respect to test preference for cv. Crocantela was no statistical difference between the samples produced in the three cropping systems and the purchase intention test, there was significant difference in purchase intent among the samples produced in hydroponic and organic system, that is, the first was most intent the second purchase. It is concluded cultivation system used for the production of lettuce influence on physical characteristics and physico-chemical plants. In this study it was possible to obtain the sensory characterization of Brunella and Crocantella lettuce cultivars. This manner, studies with these characteristics are crucial as they allow the diagnosis of these differences assisting in obtaining important information from production and post-harvest both for the active professional in the field and the consumer.